The Influence of Extraction Time and Solvent Concentration on the Production of Spinach Leaf Protein Concentrate with KOH Solvent: Pengaruh Waktu Ekstraksi dan Konsentrasi Pelarut pada Pembuatan Konsentrat Protein dari Daun Bayam dengan Pelarut KOH - Ani Purwanti; Mukasi Wahyu Kurniawati; Siswandi Waluyo (Jurnal Kimia dan Rekayasa, 2023)
This research generated several qualitative data indicating the effects of temperature extraction and pH precipitation on spinach protein concentrates. The results shows that higher extraction temperature tend to increase protein yield. At an extraction temperature of 60°C, the spinach protein yield was 23%, while at 80°C, the protein yield increased to 28%. However, extraction temperatures above 80°C led to a decrease in protein yield due to significant protein denaturation. pH precipitation was observed to have significant influence on the quality of spinach protein. Precipitation at pH 4.5 resulted in a protein concentrate with higher brightness compared to precipitation at pH 5.5 and pH 6.5. This result indicates that acidic pH is more effective in spinach protein precipitation. Qualitative data indicated that spinach protein concentrate had good physicochemical characteristics. The protein concentrate had a greenish-yellow color and a distinctive aroma of spinach leaves. It had a neutral taste and a smooth texture. spinach protein concentrate consistency can be adjusted depends on user needs through the drying process. The results of this study demonstrated potential use of spinach protein concentrate in various food products. Spinach protein concentrate can be used as a manufacturing ingredient for a variety of food products such as pasta, cakes, and other processed products. Overall, this research provides evidence that protein extraction from spinach leaves with modified temperature extraction and pH precipitation can yield high-quality spinach protein concentrate. The results of this research will serve as a basis for the development of healthy and highly nutritious vegetable protein foods, and can contribute to the improvement of public health through the intake of highly nutritious foods. AbstrakPenelitian ini bertujuan untuk membuat konsentrat protein dari daun bayam dengan pelarut KOH untuk mendapatkan hasil maksimal dengan variabel suhu ekstraksi dan konsentrasi pelarut yang digunakan. Daun bayam terlebih dahulu dibersihkan, tulang daunnya dibuang, kemudian dipotong kecil-kecil dan ditimbang sebanyak 50 gram. Proses awal yang dilakukan adalah proses ekstraksi pada suhu ekstraksi 700C dengan variasi konsentrasi pelarut KOH antara 0,1 N – 0,5 N dengan interval 0,1 N dan waktu ekstraksi yaitu antara 30 – 150 menit. Hasil yang diambil berupa filtrat. Selanjutnya dilakukan proses penggumpalan protein dengan penambahan larutan HCI 10 N pada suhu 750C, waktu 10 menit dan pH penggumpalan 4. Kemudian larutan didiamkan sampai terbentuk endapan konsentrat, disaring, dan dikeringkan dalam oven dengan suhu 400C sampai berat konstan. Hasil analisa daun bayam segar adalah sebagai berikut: kadar air 78,68%, kadar abu 1,442%, dan kadar protein 6,46%. Dari penelitian diperoleh kondisi optimum yaitu proses dengan waktu ekstraksi 90 menit dengan berat konsentrat protein maksimal 6,326% dengan kesalahan rata-rata sebesar 6,99 % dan proses dengan konsentrasi pelarut KOH 0,4 N. dengan berat konsentrat protein maksimal sebanyak 5,956 % dengan kesalahan rata-rata 10,33 %.